Effect of stimulation of the subthalamic nucleus on oral control of patients with parkinsonism. Issue 3 (1st September 1999) - Gentil, Michèle; Garcia-Ruiz, Pedro; Pollak, Pierre; Benabid, Alim-Louis
Abstract : OBJECTIVES: To assess the oral system of parkinsonian patients treated with chronic stimulation of the bilateral subthalamic nucleus (STN) to evaluate precisely the effectiveness of this procedure on the articulatory organs. METHODS: Load sensitive cantilevers were used to sample ramp and hold force contractions generated by the upper lip, lower lip, and tongue. The subject was given the instruction to produce forces as rapidly and as accurately as possible in response to the target signal (ranging from 0.25 to 2 N), which appeared on a screen. Maximal force of each effector organ was also measured. Fourteen healthy control subjects and 10 patients participated in this study. After an overnight fast the patients were evaluated in the morning under two conditions: during bilateral stimulation and 1 hour after stopping STN stimulation. RESULTS: During STN stimulation, dynamic and static control of the articulatory organs were improved: the maximal strength of the articulatory organs, their accuracy to reach the target, and the precision of the hold phase increased. In addition, the reaction time and the rise time of the ramp phase decreased. Patients' speech as assessed by the item 18 of the unified Parkinson's disease rating scale (UPDRS) was greatly improved by electrical stimulation of the STN CONCLUSIONS: Improvement of oral control of the stimulated patients suggests that STN stimulation modulates neuronal structures involved in speech. However, more patients have to be evaluated for a fuller understanding of the effect of this surgical procedure on speech.